Adam Mickiewicz - Dziady / Zaniewski. - Zaniewski, Wojciech (1955- ). (Teatr Wybrzeże, 1979)
Plakat premiery, która odbyła się 3.11.1979 r. w Teatrze Wybrzeże. Plakat przedstawia trzy męskie postacie.